Pengelolaan Manajemen Yayasan Terhadap Guru Dalam Pelaksanaan Nilai-Nilai Pancasila di Lembaga Kursus Dan Pelatihan Ayumi Kabupaten Deli Serdang - Jamillah Aqtar; Samsul Bahri; M. Faisal Husna; Disna Anum Siregar (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2025)
The Institute of Courses and Training (LKP) as part of informal education plays a crucial role in the development of human resources (HR). LKP not only functions as a place to improve learners' technical skills but also as a vehicle to internalize moral and ethical values, including the values of Pancasila. This study aims to assess the implementation of Pancasila values among teachers and learners at Ayumi Deli Serdang Course and Training Institute. The research was conducted by conducting interviews with the foundation, teachers, and students at Ayumi Deli Serdang Course and Training Institute and observations to directly observe the implementation of Pancasila values in training activities and foundation management. Overall, interviews with the three sample groups showed a strong connection between the management of the foundation management, teacher support, and the impact of learning on students in the application of Pancasila values. Observations showed the implementation of Pancasila values in various aspects of learning and management activities. The foundation's vision and mission have been reflected in the foundation's management which supports teachers in instilling Pancasila values to students. Teachers actively implement Pancasila values through contextual approaches, such as encouraging tolerance, mutual cooperation, and social justice in the classroom.